An investigation into the land tax staff's commitment, work system and appraisal: The case of Malaysian state governments - Abdul Manaf, Nor Aziah; Hasseldine, John; Hodges, Ron (2005)
The present study compared the levels of commitment to the organizations, work system and staff appraisal among 700 land tax staff working in Malaysia, using a questionnaire survey.The results indicate there are significant differences of staff organizational commitment and work system between state governments.It shows higher levels of commitment and work system result in higher levels of collection.Findings also reveal that staff commitment and work system are highly correlated with the organizational billing procedure,collection methods, managing land taxpayer accounts, enforcement and staff appraisal.